ANALYSIS OF LATERAL-TORSIONAL BUCKLING (WARPING) OF STEEL I-BEAM WITH INITIAL IMPERFECTION - Lili Shintike, Yosephine
The strength of a beam is often controlled by lateral torsional buckling boundary conditions. To calculate the type of lateral torsional buckling failure, AISC has provided equations but the equation has not taken into account the effects of initial imperfections and upper flange loading, where in practice both of these will reduce the magnitude of the structural strength of lateral torque buckling. This analysis study was conducted to see the effect of the initial imperfections and the effect of loading on the beam flange on the lateral moments of elastic and inelastic torsional bending. The elastic and inelastic lateral torque buckling phenomenon is seen by taking into account the effect of residual stresses carried out by collapse analysis using the finite element method with the help of the ADINA v9.0 program. The research that has been done has resulted that the magnitude of the reduction due to initial imperfection is a function of the magnitude of the initial imperfection and the length of the unfettered span, where the greater the initial imperfection it will cause the greater the reduction of critical moments. For the lateral elastic torque buckling conditions the increase in the length of the unfettered span will cause a reduction in the reduction that occurs, but for the inelastic region, the magnitude of the reduction is relatively constant with respect to the length of the beam span. The effect of the location of loading on the upper flange, it has been seen that the equation proposed by the SSRC Guide is suitable for use in both elastic and inelastic lateral torsional buckling conditions